PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DALAM MENCIPTAKAN LOYALITAS PELANGGAN PT. MPM MOTOR KEDIRI - Ike Widya Arini; Sumarji Sumarji (Commodities, Journal of Economic and Business, 2020)
This research is motivated by the growing of economy which is enlivened by various kinds of business competition, such as in the automotive sector. PT. MPM Kediri Motor is one of the official dealers of Honda motorcycle products that struggle to full fill the consumers need in the automotive field by carrying out the concept of better serving. In running the business, PT. MPM Motor Kediri needs to maintain customer satisfaction to create customer’s loyalty, by improving product quality and service quality that is provided to customers. The loyalty level of customers to PT. MPM Motor Kediri is still lacking or beneath of PT. MPM Kediri Motor’s target. The purpose of this research is, to determine the effect of product quality and service quality on customer satisfaction in creating customer loyalty. The research method used in this research is quantitative descriptive. The population is all customers / consumers of PT. MPM Motor Kediri, while the sample of this study is 100 customers of PT. MPM Motor Kediri who came to take the BPKB. Data collection techniques through questionnaires with the sampling technique used is the Slovin method. The analytical method used in this research is multiple regression analysis using SPSS software version 15.0, which previously the descriptive variable test, validity test, reliability test, coefficient of determination, significant test (T test and F test), multiple linear regression is tested first. Based on the results of regression analysis shows that product quality (X1) and service quality (X2) partially or simultaneously have a positive and significant effect on customer satisfaction (Y). Customer satisfaction variable (Y) partially also has a positive and significant influence on customer loyalty (Z). Based on the research results, the company is expected to increase customer satisfaction by maintaining product quality and the service quality. PT. MPM Motor must continue to control the marketed products and conduct regular evaluations or employees training or FLP in providing satisfactory services.